Comparison of Cesarean Deliveries in a Multicenter U.S. Cohort Using the 10-Group Classification System - Pasko, Daniel N.; McGee, Paula; Grobman, William A.; Bailit, Jennifer L.; Reddy, Uma M.; Wapner, Ronald J.; Varner, Michael W.; Thorp, John M., Jr.; Caritis, Steve N.; Prasad, Mona; Saade, George R.; Sorokin, Yoram; Rouse, Dwight J.; Tolosa, Jorge E.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development Maternal-Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2022)
Objective We sought to (1) use the Robson 10-Group Classification System (TGCS), which classifies deliveries into 10 mutually exclusive groups, to characterize the groups that are primary contributors to cesarean delivery frequencies, (2) describe inter-hospital variations in cesarean delivery frequencies, and (3) evaluate the contribution of patient characteristics by TGCS group to hospital variation in cesarean delivery frequencies.Study Design This was a secondary analysis of an observational cohort of 115,502 deliveries from 25 hospitals between 2008 and 2011. The TGCS was applied to the cohort and each hospital. We identified and compared the TGCS groups with the greatest relative contributions to cohort and hospital cesarean delivery frequencies. We assessed variation in hospital cesarean deliveries attributable to patient characteristics within TGCS groups using hierarchical logistic regression.Results A total of 115,211 patients were classifiable in the TGCS (99.7%). The cohort cesarean delivery frequency was 31.4% (hospital range: 19.1–39.3%). Term singletons in vertex presentation with a prior cesarean delivery (group 5) were the greatest relative contributor to cohort (34.8%) and hospital cesarean delivery frequencies (median: 33.6%; range: 23.8–45.5%). Nulliparous term singletons in vertex (NTSV) presentation (groups 1 [spontaneous labor] and 2 [induced or absent labor]: 28.9%), term singletons in vertex presentation with a prior cesarean delivery (group 5: 34.8%), and preterm singletons in vertex presentation (group 10: 9.8%) contributed to 73.2% of the relative cesarean delivery frequency for the cohort and were correlated with hospital cesarean delivery frequencies (Spearman's rho = 0.96). Differences in patient characteristics accounted for 34.1% of hospital-level cesarean delivery variation in group 2.Conclusion The TGCS highlights the contribution of NTSV presentation to cesarean delivery frequencies and the impact of patient characteristics on hospital-level variation in cesarean deliveries among nulliparous patients with induced or absent labor.Key Points
Keywords: cesarean delivery; 10-Group Classification System; Robson; nulliparous term singletons in vertex